Western boundary current system in the Weddell Sea: interplay of thermohaline gradients and wind stress forcing across seasonal scales - Pereira-Vázquez, Tania; Aguiar-González, Borja; Rodríguez-Santana, Ángel; Veny, Marta; Marrero-Díaz, Ángeles (Frontiers in Marine Science, 2025)
We investigate the seasonal dynamics of the Western Boundary Current System (WBCS) in the Weddell Gyre, focusing on the interaction between thermohaline gradients and wind stress forcing. Using high-resolution reanalysis data (GLORYS12V1) and altimetry observations, we analyze the horizontal and vertical structure of the WBCS along the extended ADELIE transect located in the northwestern sector of the Weddell Gyre, a key section in the western part of the SR04 WOCE line. Our analysis well captures the multi-jet structure of bottom-intensified currents, including the Antarctic Coastal Current (CC), Antarctic Slope Front (ASF), Weddell Front (WF), and a newly identified feature, first reported in this work, the Inner Weddell Current (IWC). Seasonal variations show maximum full-depth volume transport in autumn (40 ± 0.6 Sv) and minimum in summer (33.8 ± 3.0 Sv), with strong correlations to wind stress curl (R² 0.8). Correlation analyses indicate that wind stress forcing plays a predominant role in the IWC compared to the jets closer to the coast, where steep density gradients and topographic steering have a stronger influence. As a result, the IWC emerges as a major wind-driven component, contributing over half of the full-depth volume transport (16.2 ± 3.0 Sv out of 37.3 ± 5.0 Sv) and playing a key role in water mass recirculation within the Weddell Gyre. Throughout the water column, salinity primarily controls the density field in the upper ocean, whereas at depth, the bottom-intensified cores of the ASF and WF are solely driven in the northeastward flow direction by temperature gradients. This pattern strengthens in winter, when temperature and salinity gradients steepen over the continental slope due to deep water mass formation. In contrast, in the IWC domain, both temperature and salinity gradients contribute to the northeastward geostrophic flow. These results provide a climatological baseline for understanding the seasonal and spatial variability of the WBCS, highlighting the complementary roles of thermohaline gradients and wind stress forcing in shaping its different components.